Prevalence of risk factors for non-communicable diseases, undiagnosed diabetes and dyslipidemia among doctors as compared with age and gender matched adults in Delhi NCR: a hospital based study - Pichika, Varun S.; Tibrewal, Abhishek O.; Singh, Narinder P.; Chowdhary, Pankaj N.; Agarwal, Rajat K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Doctors, due to their work-related stress, are prone to non-communicable diseases (NCDs) risk factors (smoking, alcohol use, unhealthy diet, physical inactivity) making them vulnerable to lifestyle disorders such as obesity, diabetes, dyslipidemia etc. To compare the prevalence of NCDs risk factors, obesity, diabetes and dyslipidemia among doctors and healthy adults visiting preventive health clinic of Delhi tertiary care hospital. Methods: This was a cross-sectional study among 100 doctors and 100 healthy subjects aged 30-60 years, without coronary heart disease and pre-existing diabetes or hypertension. The variables included were socio-demographic; risk factors, and laboratory. Descriptive analysis, chi-square or fischer exact and independent t-test was used. Results: The age (mean: 42.4 vs. 44.4; p=0.14) and gender (M: 80% vs. 76%, p=0.5) were comparable between doctors and the healthy adults. The prevalence of alcohol use (75% vs. 13%, p<0.001) and physically inactivity (42% vs. 27%, p<0.001) were higher, while the prevalence of smoking (15% vs. 31%, p<0.001) was lower among doctors versus the healthy adults. The prevalence of abnormal total cholesterol (40% vs. 25%, p=0.024) was higher, while the prevalence of undiagnosed diabetes (5% vs. 18%, p=0.006), abnormal HDL (21% vs. 37%, p=0.013) and abnormal triglyceride (32% vs. 48%, p=0.021) was lower among doctors versus the healthy adults. Conclusions: The prevalence of NCDs risk factors was found to be higher among doctors versus healthy adults. Therefore, there is a need of regular health awareness and screening programs among doctors as well.